A New Model for Social Justice Supervision. (10th December 2020) - Dollarhide, Colette T.; Hale, Shiloh C.; Stone‐Sabali, Steve
Abstract : Social justice supervision honors the identities of the supervisee and the client, teaches social justice skills to the supervisee, and prioritizes social justice counseling outcomes in the supervisee's counseling work. The purpose of this article is to describe a comprehensive model for social justice supervision that mandates supervisor self‐evaluation, explores supervisees' identities and strengths, emphasizes the social justice needs of clients, and uses social justice outcomes for clients as a measure of counseling success. Implications are explored.